Safety-aware human-in-the-loop reinforcement learning with shared control for autonomous driving - Huang, Wenhui (2025)
The learning from intervention (LfI) approach has been proven effective in improving the performance of RL algorithms; nevertheless, existing methodologies in this domain tend to operate under the assumption that human guidance is invariably devoid of risk, thereby possibly leading to oscillations or even divergence in RL training as a result of improper demonstrations. In this paper, we propose a safety-aware human-in-the-loop reinforcement learning (SafeHIL-RL) approach to bridge the abovementioned gap. We first present a safety assessment module based on the artificial potential field (APF) model that incorporates dynamic information of the environment under the Frenet coordinate system, which we call the Frenet-based dynamic potential field (FDPF), for evaluating the real-time safety throughout the intervention process. Subsequently, we propose a curriculum guidance mechanism inspired by the pedagogical principle of whole-to-part patterns in human education. The curriculum guidance facilitates the RL agent's early acquisition of comprehensive global information through continual guidance while also allowing for fine-tuning local behavior through intermittent human guidance through a human-AI shared control strategy. Consequently, our approach enables a safe, robust, and efficient reinforcement learning process independent of the quality of guidance human participants provide. The proposed method is validated in two highway autonomous driving scenarios under highly dynamic traffic flows (https://github.com/OscarHuangWind/Safe-Human-in-the-Loop-RL). The experiments' results confirm the superiority and generalization capability of our approach when compared to other state-of-the-art (SOTA) baselines, as well as the effectiveness of the curriculum guidance.